A Novel Variant Of Regenerating Iα Gene (REG) In Type II Diabetics Among Pakistani Targeted Population - Saleem, Sadaf; Baig, Saeeda; Farrukh, Sadia; Shafiq, Mazhar (Journal of Rawalpindi Medical College, 2023)
Objective: Regeneration of pancreatic β-cells, is an essential step towards diabetes management. The regenerating (REG) Iα gene is secreted from damaged β-cell for the synthesis of β-cell. This study aimed to identify REG Iα gene polymorphisms and their association with Type II diabetes (T2DM). Methods: Patients (110) with T2DM and age-related controls were selected from PNS Shifa Hospital, Karachi. DNA was extracted PCR was performed and amplified products were sequenced to identify polymorphisms. For six exons of the REG 1a gene, 6 sets of primers were designed. The selected (51) samples were amplified and sequenced for 306 (51x6) times. Odds ratios were calculated through logistic regression analysis. The correlation was used to find an association between REG Iα and diseases. p< 0.05 was considered significant. Results: Blood samples were drawn from 90 finalized patients, including 70 diabetics and 20 controls with an M: F ratio of 12:8. Twenty patients opted to withdraw. The REG Iα and disease duration in type II diabetics showed a negative correlation (r= -0.355, p=0.005). The single nucleotide polymorphisms (SNPs) of eight sites were detected: g.-385T>C, g.-243T>G, g.-145G>A, g.+142A, g.+209G>T, g.+226A>G, g.+2199G>A, g.+2360A>G. The novel SNP g.-145G>A was found in all patients (controls, T2DM). Among all SNPs, only g.+209G>T showed a positive association (OR= 2.4, p=0.01) with T2DM. Whereas, g.-243T>G showed a positive association (OR=8.06, p=0.0003) with smoking. Conclusion: A novel variant g.-145G>A REG Iα gene was found among all participants. The SNPs g.+209G>T had a significant positive association with T2DM and SNP g.-243T>G showed an increased risk of the disease among smokers. Keywords: REG Iα gene, Type II diabetes, β-cells regeneration, Polymorphisms.